Magic, Demons, and Heretics: Three Puzzling Cases in The Letter of Euthymius of Akmonia - Slavova, Mirena (Studia Ceranea, 2025)
This study explores the theme of magic and demons in the anti-heretical Letter written by Euthymius, an 11th-century monk from the Monastery of Theotokos Perivleptos in Constantinople. The Letter was aimed at his fellow countrymen from Acmonia and primarily targeted the Phundagiagites, also known as the Bogomils, along with the Armenians. Given the significant role of the demonic nature of heresies in his accusations, it is crucial to examine the Christian Church’s perception of how heretics are believed to communicate with demons.The paper argues that Euthymius used accusatory arguments about demons in two main ways: first, through a general characterisation of heresies, and second, by recounting several fictional stories involving levitation, lycanthropy, lecanomancy, and teleportation. It aims to provide an interpretation of three of these stories that have been previously misunderstood or overlooked in research: the desecration of a newly constructed church by a priest at Hieron, the lecanomancy involving teleportation performed by a magus for the heretic Lycopetros, and the unsuccessful attempt at teleportation by Terevinthos.By analysing these cases, the author aims to deepen our understanding of the rhetorical strategy of heresiological texts, which incorporate narratives about sacrilege, magic, and demons to condemn heresies.